COMENTÁRIOS SOBRE A ESTRUTURA FONOLÓGICA DOS DITONGOS NASAIS NO PORTUGUÊS DO BRASIL - Wetzels, W. Leo (Revista de Letras, 2016)
COMENTÁRIOS SOBRE A ESTRUTURA FONOLÓGICA DOS DITONGOS NASAIS NO PORTUGUÊS DO BRASIL